Changes in Salivary pH After Consuming Sorghum-Based Non-Cariogenic Biscuits - Subekti, Ani Subekti; Wiradona, Irmanita; Dyah Utami, Wahyu Jati; Rinawati, Listyo; Wahyuningtyas, Miranda Gita (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
The degree of acidity of saliva is influenced by the consumption of carbohydrate-containing foods. Daily food consumed by school children at home and outside the home is cariogenic food containing many carbohydrates. Children like sweet biscuit snacks. Sorghum-based biscuits are a healthy snack for school children. Sorghum biscuits contain xylitol compounds and are sugar-free. The purpose of this study was to determine changes in salivary pH after consuming non-karyogenic biscuits made from sorghum in elementary school children. This type of study was an experiment with 3 treatment groups and 1 control group. There are 4 groups: sorghum biscuits, 100% xylitol biscuits, 50% xylitol biscuits, and the control group. The design of this study is pre and post-test experiment design, namely the degree of acidity (pH) saliva pre-test is carried out before consuming biscuit snacks, while the post-test is carried out consuming biscuit snacks. Salivary pH measurement using a pH meter. Statistical test to determine the effect of consuming all 4 biscuits using the one-way ANOVA test. The result of glucose content in 50% xylitol biscuits is the lowest at 2.38%. Consuming biscuits with low glucose levels causes a slight decrease in salivary pH compared to consuming biscuits with high glucose levels. Sorghum-based biscuits are the best for dental health because they slightly lower the pH of saliva. But children dislike sorghum biscuits the most. This study concludes that 100% xylitol biscuits can lower salivary pH slightly low and are liked by elementary school children.Â